Osteoid Osteoma of the Sacrum Mimicking Sacroiliitis: A Case Report - Gürkan ÖZKOÇ (Archives of Rheumatology, 2013)
A 23-year-old female patient admitted with continuous pain localized in her right sacroiliac joint for four months. She had been diagnosed with sacroiliitis in another clinic. Her plain radiographs, bone scintigraphy and laboratory tests were normal. Magnetic resonance imaging showed a nonspecific edema of the bone marrow at the posterior corner of the sacrum which had been misdiagnosed as sacroiliitis. Computed tomography (CT) showed a nidus located posteriorly at the S2 vertebra of the neighboring sacroiliac joint. A removal of the nidus and pathological examination revealed a diagnosis of osteoid osteoma. Although osteoid osteoma is a very rare entity in the differential diagnosis of sacroiliac pain, it should be kept in mind in the presence of aching pain which is refractory to conservative treatment and responsive to nonsteroidal anti-inflammatory drugs. Magnetic resonance imaging is not always diagnostic, whereas CT is more helpful for diagnosing osteoid osteoma.